An Algorithm for Diagnosing and Treating Primary and Recurrent Patellar Instability. Issue 9 (13th September 2016) - Duerr, Robert A.; Chauhan, Aakash; Frank, Darren A.; DeMeo, Patrick J.; Akhavan, Sam
Abstract : Major anatomic risk factors for recurrent patellar instability include trochlear dysplasia, patella alta, a lateralized tibial tuberosity, and medial patellofemoral ligament insufficiency. Acute first-time patellar dislocation may be treated nonoperatively in the absence of osteochondral injury. Recurrent patellar instability often requires medial patellofemoral ligament reconstruction, with osseous procedures reserved for patients with substantial underlying anatomic abnormalities. Surgical treatment of patellar instability is complex and should be individualized to address the needs of each patient.